COMPARATIVE STUDY OF FIQH EDUCATION ON WAQF IN MALAYSIA AND INDONESIA - Ab Hamid, Muhammad Hamizan; Hayati, Nur Rohmah (Jurnal As Sibyan, 2024)
This research investigates the comparative approach to fiqh education on waqf in Malaysia and Indonesia, focusing on curricular structures, pedagogical approaches, learning materials, and governance frameworks. This study uses a qualitative research technique with a comparative analytical lens to conduct document reviews, expert interviews, and field observations at Islamic higher education institutions. The findings show that Malaysia uses a systematic and regulatory-backed framework to integrate fiqh education into a centralized governance architecture. In contrast, Indonesia employs a decentralized and flexible strategy, allowing for more curricular flexibility that is consistent with regional socio-cultural circumstances. The study emphasizes the importance of combining traditional Islamic legal concepts with modern educational governance to improve the effectiveness and accessibility of waqf-related fiqh education. The study makes practical recommendations to improve the sustainability and efficacy of waqf education in both nations, focusing on digital transformation, policy alignment, and the importance of international cooperation.